Autoimmune manifestation of hepatitis C virus infection as a risk for late virological relapse after pegylated interferon and ribavirin therapy - Ružić, Maja; Fabri, Milotka; Preveden, Tomislav; Bačulov, Katarina; Pete, Maria; Stojšin, Anja Jasna (Vojnosanitetski pregled, 2021)
Introduction. We are aware of the risk of late virological relapse (LVR) years after sustained viral response (SVR) by pegylated interferon and ribavirin alfa (PegIFNa + RBV) of chronic hepatitis C viral (HCV) infection. We presented three patients with LVR, treated by PegIFNa and ribavirin 5 years after the SVR was established. Case report. We analysed 129 (38.8% female, 61.2% male, mean age 37.02 ± SD 11.99) patients treated for chronic HCV with PegIFNa + RBV, with at least 5 years from the establishment of SVR. In addition to the biochemical parameters of liver function, the qualitative HCV RNA polymerase chain reaction (PCR) and the quantitative PCR HCV RNA test were made. Five years after establishing SVR in 2.3% (3/129) of patients, the relapse of HCV infection was registered by qualitative and quantitative PCR HCV RNA assay and all of these patients had additional autoimmune diseases: vasculitis, autoimmune hepatitis, and vasculitis of central nervous system. Conclusion. The existence, but low rate of LVR HCV infection was confirmed, dominantly in patients with additional autoimmune diseases. Due to this SVR after therapy by PegIFNa + RBV should be considered as an indicator of successful HCV suppresion, not its complete eradication.